Mémoire, récits et héritage de la Révolution de 1848 à Venise - Eva Cecchinato (Laboratoire Italien)
1848 in Venice was one of the most important experiences of the two revolutionary years (1848-1849) in Italy and Europe. However, in the following decades, the narration of the events didn’t valorize its revolutionary character and its democratic heritage. The comparison with the Roman Republic of 1849, which had great importance in the French political debate over the events, was one of the fundamental aspects of these re-readings, which in some cases led to represent the Government of Daniele Manin as the rightful restoration of former Republic of San Marco. If during the third Austrian rule (1849-1866) the last revolutionary experience was represented as the result of a meeting of criminals who had enlisted the Venetian people, during the Liberal era, public use of history was adapted alternately by the dominant forces: the moderates who led the city of Venice, the alliance between conservative clerics and then the “Adriatic nationalism”.